FAILURE RISK ANALYSIS GLASS BOWL PRODUCTION PROCESS USING FAILURE MODE EFFECT ANALYSIS AND FAULT TREE ANALYSIS METHODS (A CASE STUDY) - Ikhwan Syahtaria; Ali Mashudi; Bambang Suharjo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2018)
Product defects are a natural thing in a production process, but it would be better to avoid them. XYZ Industries is a company that produces glassware in the form of the glass bowl. The production failure experienced by this company is still high at 3.1% of the total production while the defect target that the company wants is 2%. The purpose of this study was to identify the types of defects that occur in glass bowl products on the production floor based on the results of searches of literature studies and deep interviews with employees, get the risk of failure of the largest production process in the RPN (Risk Priority Number) value of the FMEA method then analyzed again using the FTA method and determine the proposed improvements needed based on the analysis of defects that occur in glass bowl products, thus minimizing product defects and increasing company profits. In this study using the method of Failure Mode and Effect Analysis (FMEA) and the Fault Tree Analysis (FTA) method to identify failures that occur and provide prevention solutions. Based on the results of data processing, the proposed improvements given to the company as a whole are the company in order to pay more attention to the maintenance of the machine so that the machine can avoid the failure of its function